Resistance Against Colonialism in Abdul Hamid al-Farahi’s Poetry During the Fall of the Ottoman Empire - Izza Vithry Hayah; Laily Fitriani; Halimi Zuhdy (Islah: Journal of Islamic Literature and History, 2025)
The dissolution of the Ottoman Empire in the early 20th century shook the Islamic world, worsened by Italy’s Colonial Conquests of Tripoli (1911–1912). This study examines the representation of history in an Arabic poem by the Indian poet Abdul Hamid al-Farahi, titled Fī Taṭāwul al-Ṭalyān ʿalā Ṭarābulus, using Stephen Greenblatt's New Historicism. The research uncovers how al-Farahi’s poem serves as a literary response to the fall of the Ottoman Empire during Italian colonial aggression. The historical context is analyzed in parallel with poetic expression within the New Historicism framework. The method used is descriptive-qualitative with the following stages: (1) repeated close reading, (2) translation of verses, (3) identification of historical symbols, and (4) thematic classification. Data analysis involves (1) parallel reading between the poem and historical texts and (2) interpretation based on subthemes. The results show that the poem reflects themes of colonization, the suffering of the Muslim community, the trauma of invasion, and a call to defend religious and national dignity. Through New Historicism, the study demonstrates that literature and historical narratives are interconnected, and that al-Farahi’s poem can be read as a historical form of resistance against colonial oppression.